Spectrum and dosing of urate-lowering drugs in a large cohort of chronic kidney disease patients and their effect on serum urate levels: a cross-sectional analysis from the German Chronic Kidney Disease study - Kielstein, Jan T.; Heisterkamp, Markus; Jing, Jiaojiao; Nadal, Jennifer; Schmid, Matthias; Kronenberg, Florian; Busch, Martin; Sommerer, Claudia; Lorenzen, Johan Matthes; Eckardt, Kai-Uwe; Köttgen, Anna (Clinical kidney journal, 2021)
Despite a plethora of studies on the effect of urate-lowering therapy (ULT) in patients with chronic kidney disease (CKD), current guidelines on the treatment of hyperuricaemia and gout vary, especially concerning the need for dose adjustment of allopurinol, whose main metabolite is accumulating with declining renal function. Data on allopurinol dosing and its relationship to renal function, co-medication and sex and the resulting urate level in large cohorts are missing.We studied a subgroup of 2378 patients of the German Chronic Kidney Disease (GCKD) study to determine prescription patterns of ULT among CKD patients under nephrological care and the relationship of ULT dose to urate levels. Prescription and dosing of ULT were manually abstracted from the patient’s paper charts at the baseline visit, in which all currently used medications and their dosing were recorded.In this cohort, 39.6% were women, the mean estimated glomerular filtration rate (eGFR) was 51.3 ± 19.3 mL/min/1.73 m2 and the mean age was 59.0 ± 12.4 years. Of the 2378 examined patients, 666 (28.0%) received ULT. The dose of ULT was available for 572 patients. The main ULT agent was allopurinol (94.4%), followed by febuxostat (2.9%) and benzbromarone (2.6%). Of the 540 patients who used allopurinol with a reported daily dose, 480 had an eGFR <60 mL/min/1.73 m2 and 320 had an eGFR <45 mL/min/1.73 m2, 31.5% of the latter (n = 101) received a dose >150 mg/day, the recommended maximal dose for this level of eGFR. The prescribed dose was not related to eGFR: the median eGFR for patients taking 100, 150 and 300 mg/day was 40 [interquartile range (IQR) 32-49], 43 (34-52) and 42 (35-54) mL/min/1.73 m2, respectively. Patients with lower doses of allopurinol had higher serum urate levels than patients with higher (than recommended) allopurinol doses. Sex, alcohol intake, eGFR, use of diuretics and treatment with allopurinol were independent determinants of serum urate levels in multivariate regression analysis.The most frequently used drug to lower serum urate levels in this CKD cohort was allopurinol. Even in patients regularly seen by nephrologists, the dose of allopurinol is often not adjusted to the current eGFR. Patients with higher ULT doses achieved better control of their serum urate levels. Lowering of serum urate in CKD patients requires balancing potential adverse effects of allopurinol with suboptimal control of serum urate levels.